2017
DOI: 10.18203/2349-3291.ijcp20174748
|View full text |Cite
|
Sign up to set email alerts
|

The profile of Blood Pressure (BP) and the prevalence of Hypertension in school going children aged 5-15 years of Manipur, a North-Eastern hilly Indian state

Abstract: Background: Changing trend in lifestyle and increasing incidence of obesity in children may have a bearing on increasing incidence of adulthood hypertension. Recognition and timely intervention of childhood hypertension at the early stage may be the best strategy to decrease the burden of hypertension in the adult. Methods: This is a cross sectional study where school going children aged 5-15 years of age were examined physically and by 2D color Doppler Echocardiography. Children with systemic illness or any h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…It showed 15.3% high prevalence of hypertension among the school going children aged 5-15 years of Manipur. [18] Similar to this, another study from Imphal showed 15.7% prevalence of hypertension among students of higher secondary. [24] In contrast to this, many other studies done in different regions showed the prevalence of hypertension in the school going children to be in the range of 3-10%.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It showed 15.3% high prevalence of hypertension among the school going children aged 5-15 years of Manipur. [18] Similar to this, another study from Imphal showed 15.7% prevalence of hypertension among students of higher secondary. [24] In contrast to this, many other studies done in different regions showed the prevalence of hypertension in the school going children to be in the range of 3-10%.…”
Section: Discussionsupporting
confidence: 69%
“…Studies done in India and also in various other countries had similar findings to the present study. [18,[30][31][32][33] One of the studies done by Jena et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study of school going children in age group 5 -15 years of age, the prevalence of prehypertension and hypertension were 17.5% and 15.3% respectively. 16 Sathish Kumar et al, in their study found the prevalence of hypertension among age group of ≥ 25 years in 2 urban communities of Imphal to be 37%. 17 Studies in rural area of Manipur found prevalence of hypertension and prehypertension to be 25% and 14.3% respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Further, the estimated pooled prevalence of adolescent hypertension in India is 7.6% (Daniel et al, 2020). Such researches have been lacking in Northeast India, where very few studies on child obesity and adolescent hypertension have come up (Borah et al, 2015; Thangjam et al, 2017). Ethnically, this region's people are closer to East Asians, having similar physical and physiological characteristics.…”
Section: Introductionmentioning
confidence: 99%